Specific Parameters of Extracellular Matrix Remodeling of Liver and Lungs of Mice with BCG Granulomatosis during Chronic Inflammation Depending on the Method of Administration of Liposomal Oxidized Dextran - L. B. Kim; А. N. Putyatina; G. S. Russkikh; V. А. Shkurupy (Туберкулез и болезни лёгких)
The objective: to study the effect of liposomal oxidized dextran (LOD) on remodeling of the extracellular matrix of organs of mice during the period of chronic BCG granulomatosis and effects of LOD on this process depending on the route of administration.Subjects and Methods. The liver and lungs of mice with BCG granulomatosis were studied using different methods of LOD administration (intraperitoneally and by inhalation). The content of glycosaminoglycans, hydroxyproline fraction, the activity of matrix metalloproteinases (MMPs), hyaluronidases and a2-macroglobulin, and the content of tissue inhibitors of MMPs (TIMP-1 and -2) were evaluated.Results. The administration of LOD to mice infected with the BCG vaccine suffering from chronic granulomatosis with severe fibrosis (6 months after infection for 3 months) resulted in the aggravation of collagen degradation in the liver. In the lungs, along with increased collagen degradation, decreased collagen synthesis was observed. It was apparently due to suppressed activity of a2-macroglobulin and decreased content of TIMP-1 and -2. In the liver, with intraperitoneal administration of LOD, signs of suppressed fibrogenesis and fibrolysis were observed versus the data obtained for inhalation administration. There were no differences in the content of hydroxyproline fractions in the lungs depending on the method of LOD administration. Thus, administration of LOD to mice led to lower severity of fibrosis while the mechanisms of fibrolysis in the lungs and liver differed.